2020
DOI: 10.1093/jxb/eraa388
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation and genomic prediction of growth, physiological traits, and nitrogen-use efficiency in perennial ryegrass under low-nitrogen stress

Abstract: Genomic prediction of nitrogen use efficiency (NUE) has not been studied in perennial grass species exposed to low N stress. The experiment was designed to conduct genomic prediction of physiological traits and NUE in 184 global accessions of perennial ryegrass (Lolium perenne L.) in response to the normal (7.5 mM) and low (0.75 mM) N supply. Significant variations in plant height (ΔHT), leaf fresh weight (LFW), leaf dry weight (LDW), chlorophyll index (Chl), chlorophyll fluorescence, leaf N and carbon (C) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Improving a plant's capacity to acquire and use nitrogen more efficiently may be the key to improving performance in poor nutrient conditions (Han et al, 2015;Tegeder and Masclaux-Daubresse, 2018;Swarbreck et al, 2019). Similar to results from ryegrass (Zhao et al, 2020), sunflower was found to generally increase nitrogen utilization efficiency under nutrient limitation (Fig 2a). Moreover, contrary to RGR, the magnitude of this increase was unrelated to NUtE under benign conditions.…”
Section: Higher Nitrogen Utilization Efficiency Is Associated With Gr...mentioning
confidence: 51%
“…Improving a plant's capacity to acquire and use nitrogen more efficiently may be the key to improving performance in poor nutrient conditions (Han et al, 2015;Tegeder and Masclaux-Daubresse, 2018;Swarbreck et al, 2019). Similar to results from ryegrass (Zhao et al, 2020), sunflower was found to generally increase nitrogen utilization efficiency under nutrient limitation (Fig 2a). Moreover, contrary to RGR, the magnitude of this increase was unrelated to NUtE under benign conditions.…”
Section: Higher Nitrogen Utilization Efficiency Is Associated With Gr...mentioning
confidence: 51%
“…For instance, RR-BLUP or G-BLUP is now very commonly used to predict several complex traits in maize ( Guo et al, 2012 ; Hao et al, 2019 ; Beyene et al, 2021 ). Several NUE traits like chlorophyll index, chlorophyll fluorescence and leaf N content were also selected by genomic prediction before integrating into NUE breeding programs in ryegrass ( Zhao et al, 2020 ). In the present study, GS was performed on GY and other agronomic traits evaluated under optimum and low soil N stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…As a promising new breeding method, GS has been applied to the prediction of heterosis of various crops such as rice [11,12,16], corn [17], barley [18], wheat [19], ryegrass [20], and pumpkin [21]. The traits which were predicted in the different studies were not only limited to yield and yield components [16][17][18][19][20][21], but also those traits such as biotic-and abiotic-stress tolerances [22,23], nutrient utilization efficiency [24,25]. Compared with the previous GS studies on other crops, our research had the following characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the previous GS studies on other crops, our research had the following characteristics. First, the genetic information used in our study involves 4.44 million SNPs, which were 2-3 orders of magnitude more than the number of molecular markers used in the previous studies [16][17][18][19][20][21][22][23][24][25]. The previous studies either involved resequencing data of the crops with much smaller genomes such as rice [11,12,16], or only a small part of genome-wide SNPs of the crops with larger genomes such as barley [18] and corn [17].…”
Section: Discussionmentioning
confidence: 99%